The Effectiveness of the Golek Garwo Matrimonial Tradition in Forming Harmonious Families - Rizky Ardiansyah Hasibuan; Muhammad Muhajir (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This article examines the effectiveness of the Golek Garwo matchmaking initiative organized by the Forum Ta'aruf Indonesia in facilitating the formation of harmonious families. The Golek Garwo event took place in Sewon Bantul Yogyakarta. This study adopts a descriptive-analytical approach within the field research category. The primary data is sourced from alumni who have maintained successful marriages for 5 to 7 years. The findings indicate that the Golek Garwo program, managed by the Forum Ta’aruf Indonesia, has effectively contributed to the formation of harmonious family dynamics through arranged marriages. Predominantly, religiosity emerged as the principal determinant of marital harmony. Besides religiosity, several other supporting factors, including partner adjustment, effective communication, mutual openness, mutual understanding, and collaborative problem-solving, also strengthen marital cohesion